Yield and Chemical Composition of Marandu Grass Fertilized with Macro-and Micronutrients at Planting and for Pasture Maintenance - Amim Vieira, Maycon [UNESP]; Barreto, Ivan [UNESP]; de Marcos Lapaz, Allan; dos Santos Batista Bonini, Carolina [UNESP]; Filho, Cecílio Viega Soares [UNESP]; Moreira, Adônis; Heinrichs, Reges [UNESP] (Taylor & Francis, 2023)
The conditions in tropical regions are favorable for growth of Urochloa brizantha, but inadequate management can make the forage highly susceptible to degradation, so that the pasture quantity and quality are very poor. The objective of this study was to evaluate the effects of fertilization at planting and for maintenance of U. brizantha cv. “Marandu” pasture, consisting of phosphorus (P) and potassium (K) associated with sulfur (S), boron (B) and zinc (Zn) on forage yield and the morphological and chemical composition. The experiment was carried out in a Typic Ultisol, and the experiment was arranged in a randomized block design, with four replicates and eight treatments. In the PK treatments, rates of 80 kg ha−1 P2O5 plus 50 kg ha−1 of K2O were applied. In all treatments, 120 kg ha1 of N was applied as ammonium nitrate split in four (4 × 30 kg). In the treatment with N fertilization only, the dry weight of U. brizantha was in the lowest yield group in all evaluations of the 2-year period. The total dry weight and leaf yield of U. brizantha was strongly and positively correlated with P, K, and S application, moderately correlated with B, and weakly with Zn supply. The soil and fertilization, climate and management conditions of forage cuts were favorable for the U. brizantha yield, with a high leaf/stem + sheath ratio (>1.94), i.e, an indicator of high leaf yield. The contents of neutral and acid detergent fiber did not vary according to the type of fertilization and that of crude protein varied only slightly in the first year in forage samples of the dry period.
Keywords: Acid detergent fiber; dry weight; neutral detergent fiber; pasture; protein; Urochloa brizantha